2022
DOI: 10.3390/toxins14070503
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol Biosynthesis in Fusarium pseudograminearum Significantly Repressed by a Megabirnavirus

Abstract: Deoxynivalenol (DON) is a mycotoxin widely detected in cereal products contaminated by Fusarium. Fusarium pseudograminearum megabirnavirus 1 (FpgMBV1) is a double-stranded RNA virus infecting Fusarium pseudograminearum. In this study, it was revealed that the amount of DON in F. pseudograminearum was significantly suppressed by FpgMBV1 through a high-performance liquid chromatography–tandem mass spectrometry (HPLC-MS/MS) assay. A total of 2564 differentially expressed genes were identified by comparative trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Virus infection is known to trigger RNA silencing in plants and fungi. 11 , 34 , 35 , 36 , 37 Thus, we focused on virus effects on host genes related to RNA silencing. In A. flavus , genes involved in the RNA silencing system were not defined; thus, we searched for candidate genes by referring to the genes of A. nidulans and A. fumigatus .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Virus infection is known to trigger RNA silencing in plants and fungi. 11 , 34 , 35 , 36 , 37 Thus, we focused on virus effects on host genes related to RNA silencing. In A. flavus , genes involved in the RNA silencing system were not defined; thus, we searched for candidate genes by referring to the genes of A. nidulans and A. fumigatus .…”
Section: Resultsmentioning
confidence: 99%
“…Besides phenotypic evaluation, comparative transcriptome analyses have been conducted between virus-infected and -free isolates in several studies. 10 , 11 , 25 , 26 These reports demonstrated that mycoviruses drastically affect host gene expression, regardless of the phenotypic changes observed between the virus-infected and -free isolates. Although reports of transcriptomic analyses are accumulating, comparisons of inter-laboratory and different virus-related data have been difficult to make when attempting to extract key factors for virus effects on host cells.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, FgV1 and FgHV2 infections can reduce DON production in F. graminearum 226 , 227 . Li et al 228 found that FpgMBV1 eliminates DON accumulation by downregulating the expression of TRI biosynthetic genes. However, most research in this area is still in the laboratory stage and has not been applied in the field.…”
Section: The Management Strategy For Fusarium Myco...mentioning
confidence: 99%
“…Cryphonectria parasitica, an ascomycetes fungus, causative agent of chestnut blight [64,65], which has been a catastrophe for Castanea dentata (American chestnut) in together North America as well as Europe [66,67]. Cryphonectria hypovirulence virus-1 CHV1 is hypovirulence-related mycovirus of the C. parasitica and it was initially investigated in 1991 [68][69][70]. Knowing the biological features of CHV1, International Committee on Taxonomy of Viruses (ICTV) recognized a new family Hypoviridae [71,72].…”
Section: Mycoviruses Infecting Cryphonectria Parasiticamentioning
confidence: 99%